Eksplorasi Pengalaman Mahasiswa PGSD terhadap Keterampilan Mendengarkan dalam Cerita Kearifan Lokal pada Mata Kuliah Pembelajaran Bahasa Indonesia Kelas Lanjut di Universitas Muhammadiyah Makassar - Andi Muhammad Barkah Ambarsyah; Besse Syukroni Baso (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study was to explore the experiences of elementary school teacher education (PGSD) students at Muhammadiyah Makassar University which took place over seven weeks from November to December 2024. This research uses descriptive qualitative research to observe and analyze the listening skills of 5th semester elementary school teacher education students at Muhammadiyah Makassar University. Based on the results of this study conducted by researchers, it can be concluded that the experience of 5th semester students of elementary teacher education is quite satisfactory even though there are several obstacles they experienced when taking the results of the test sheets conducted by researchers.